Combined high hydrostatic pressure and thermal treatments fully inactivate trypsin inhibitors and lipoxygenase and improve protein solubility and physical stability of calcium-added soymilk - Manassero, Carlos Alberto (2016)
The objective of this work was to assess the possibility of obtaining calcium-added soymilk with acceptable characteristics regarding protein solubility and physical stability, and inactivation of trypsin inhibitors and lipoxygenase, through a combined thermal-high hydrostatic pressure treatment. A Doehlert design was applied to study the effect of combining pressure levels (500–700 MPa), initial temperatures (45–65 °C) and CaCl2 concentrations (5–15 mmol L− 1). Results showed that protein solubility was a function of CaCl2 concentration (p < 0.005), and that inactivation of trypsin inhibitors was a function of pressure level and temperature (p < 0.005). Lipoxygenase activity was fully inactivated in most of the conditions tested. Physical stability was improved by the combined treatments: depending on calcium concentration, either no settling was detected in a 5-day period or a less conspicuous phase separation was observed. Our results indicate that some combined thermal-high hydrostatic pressure treatments allow the preparation of calcium-enriched soymilks with improved physical stability without additives such as chelating agents, and acceptable in terms of full inactivation of trypsin inhibitors and lipoxygenase.